PROSEDUR AUDIT UMUM ATAS ASET TETAP RUMAH SAKIT UMUM DAERAH I.A MOEIS SAMARINDA - Zsa zsa Frinovisar Utami; Martinus Robert Hutauruk; Umar Hi Salim (University of Widya Gama Mahakam Samarinda, 2019)
The purpose of this study was to identify the general audit procedures on fixed assets presented by Rumah Sakit Umum Daerah I.A Moeis if it has been performing conformably to Statement of Financial Accounting Standards No. 16. It used audit paper analysis as audit program of fixed assets, internal control questionnaires, top schedule, supporting schedule and adjustment journal. The result of this study showed that the presentment of fixed assets in Rumah Sakit Umum Daerah I.A. Moeis have been performed conformably to Statement of Financial Accounting Standards No. 16. The internal control of fixed assets in Rumah Sakit Umum Daerah I.A. Moeis was good. The accounting policy of fixed assets including recognition, measurement, disclosure, and presentment of fixed assets were appropriate based on Statement of Financial Accounting Standards No. 16. However, it has been found in audit findings that Rumah Sakit Umum Daerah I.A. Moeis has not increase yet the fixed assets such as equipment, machine, and the buildings